Co-operative receiverships and its problems - Abd. Aziz, Azlina (1987)
The major reasons for the failures of the 2k Deposittaking Co-operatives (DTCs) are recession, unregulated growth of the DTCs, mismanagement and corruption, precedence of politics over professionalism, precedence of profits over service and common welfare and the lack of supervision of the dabatan Pembangunan Koperasi (JPK). There are many aspects of the situation that could be covered, i.e. the DTCs point of view, the receivers' point of view, and the publics point of view. This research paper deals with only the receivers' point of view. Thus, the materials presented in this research paper will outline the Co-operative movements in general, the receivers of the Co-operatives and the problems faced by the receivers. The context contained herein are from interviews and related literatures.